Formulation optimization of palm-based nanoemulsion containing levodopa, an anti-parkinson’s drug - Zainol, Syafinaz (2014)
The great challenges in drug delivery to the brain is the existence of blood-brain barrier (BBB) which controls the drug penetration to the brain, hence limiting the therapeutic effect of the drug for treatment of BBB diseases such as Parkinson’s disease. An anti-Parkinson’s drug, levodopa is the “gold standard” of anti-parkinsonian therapy. Only a small fraction of levodopa reaches the brain, since most is decarboxylated by enzymes and is taken up by skeletal muscle, liver, and kidney. The alternative to increase the effectiveness of levodopa is by application of efficient drug carrier systems such as nanoemulsion, solid lipid nanoparticle and liposome through parenteral delivery. Nanoemulsion is one of the potential strategies for efficient delivery of levodopa across BBB due to advantages such as nano-sized, biocompatible, biodegradable and physically stable. Various types of emulsion composition, excipients and emulsification methods were studied to produce formulation with desirable properties. High energy emulsification method was the best method to form nanoemulsions when compared to low energy emulsification method. Lecithin and Cremophor EL found to be the most suitable surfactant and co-surfactant, respectively, for the formation of stable formulation. Response surface methodology (RSM) was utilized to investigate the influence of the main emulsion composition; mixture of palm oil and medium-chain triglyceride (MCT) oil (6%–12% w/w), lecithin (1%–3% w/w), and Cremophor EL (0.5%–1.5% w/w) as well as the preparation method; addition rate (2–20 mL/min), on the physicochemical properties of palm-based nanoemulsions. The response variables were the three main emulsion properties namely : particle size, zeta potential and polydispersity index. Optimization of the four independent variables was carried out to obtain an optimum formulation palm-based nanoemulsion. The response surface analysis showed that the variation in the three responses could be depicted as a quadratic function of the main composition of the emulsion and the preparation method. The experimental data could be fitted sufficiently well into a second-order polynomial model. Nanoemulsions with particle size of 107 nm, zeta potential of -31.4 mV, polydispersity index of 0.174, viscosity of 1.6 cps were successfully produced. The Transmission Electron Microscopy (TEM) analysis revealed that the nanoemulsion droplets were spherical in shape and homogenous in distribution. The entrapment efficiency study exhibited that 43.99 % levodopa was present in the oil phase of nanoemulsion. The in vitro drug release profile suggested that there was sustained release of the levodopa from the nanoemulsion system. The nanoemulsion loaded with levodopa exhibited highest cell viability for the cytotoxicity study compared to levodopa solution. The optimized formulation was stable for 11 months at 4 °C. The studies demonstrated the feasibility of palm-based nanoemulsion system as the parenteral levodopa delivery system.